2017
DOI: 10.3324/haematol.2016.154062
|View full text |Cite
|
Sign up to set email alerts
|

Resistin induces multidrug resistance in myeloma by inhibiting cell death and upregulating ABC transporter expression

Abstract: Despite advances in therapy, multiple myeloma remains incurable, with a high frequency of relapse. This suggests the need to identify additional factors that contribute to drug resistance. Our previous studies revealed that bone marrow adipocytes promote resistance to chemotherapy in myeloma through adipocyte-secreted adipokines, but the mechanism underlying this effect and the specific adipokines involved are not well understood. We proposed to determine the role of resistin, an adipokine that is secreted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…One of the important functions attributed to resistin signaling is its ability to induce resistance to chemotherapy (Liu et al, ; Pang et al, ; Slomian et al, ). We, therefore, checked for such activity of resistin in pancreatic cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the important functions attributed to resistin signaling is its ability to induce resistance to chemotherapy (Liu et al, ; Pang et al, ; Slomian et al, ). We, therefore, checked for such activity of resistin in pancreatic cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…In the initial reports published about a decade back, resistin was evaluated in breast (Kang, Yu, & Youn, ), prostate (Housa et al, ), lung (Karapanagiotou et al, ), colorectal (Wagsater, Mumtaz, Lofgren, Hugander, & Dimberg, ), and gastric (Nakajima et al, ) cancers and the overall impression was that it is a factor worth further studies and there were observations supporting its possible use as a diagnostic marker, expression levels of which also seemed to differ in patients with varying clinical stages. In the last decade, resistin has been studied in endometrial (Hlavna et al, ), chondrosarcoma (Tsai et al, ), myeloma (Pang et al, ), and renal (Kallio et al, ) cancer models, in addition to many more reports in cancers mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…Adipocytes residing in the BM directly interact with myeloma plasma cells [39] and protect them against apoptosis induced by anti-myeloma chemotherapy [85][86][87]. MM plasma cells induce BM resident adipocytes to release lipids, which are subsequently utilized as energy for tumor cell proliferation [39].…”
Section: Adipocytesmentioning
confidence: 99%
“…MM plasma cells induce BM resident adipocytes to release lipids, which are subsequently utilized as energy for tumor cell proliferation [39]. Moreover, adipocytes produce and secrete adipokines, that stimulate MM plasma cell growth through activating JAK/STAT-PI3K/AKT pathway [87], and resistin, which inhibits myeloma cell apoptosis and promotes ATP-binding cassette (ABC) transporters expression [86]. ABC overexpression is a well-known mechanism of multidrug resistance in various cancers [88].…”
Section: Adipocytesmentioning
confidence: 99%
“…Low resistin levels were found to be associated with increased risk (Dalamaga et al, ) particularly in men (Santo et al, ). However, Pang et al, () demonstrated that resistin could play a role in drug resistance, abrogating chemotherapy‐induced apoptosis in myeloma cells via the inhibition of chemotherapy‐induced caspase cleavage. Taken together these two studies suggest that resistin could be protective against early stages of disease development, whereas detrimental in later stage.…”
Section: Adipokines: Good or Bad?mentioning
confidence: 99%